Effect of Thermal Ageing on Changes in Modulus of Elasticity E Measured by Ultrasound, Bending Test and EBSD - Vesela, Jana; Benes, Petr; Bricin, David (Manufacturing Technology Journal, 2025)
The materials used in VVER nuclear power plants are subject to thermal ageing in operation, among other degradation mechanisms. The aim of the experiment was to verify the effect of thermal ageing on the change of ultrasound velocity on the extracted parts of main circulation piping and pressurizer surge line made of austenitic steels. Two steel conditions were evaluated, as received and thermally aged. The research was carried out on samples made from non-operated pipelines and samples from pipelines after 28 years of operation. The samples were subjected to thermal ageing at 450 °C in an atmospheric furnace with a specified exposure time to simulate extended operation of the compo-nent for 60 years, where 1 year of operation means 10 months at 100 %-unit power and 2 months in shutdown. The samples were subjected to ultrasonic property measurements and the longitudinal and transverse wave velocities obtained are further used to calculate the Poisson's constant and elastic modulus E of the material. To verify the ultrasonic measurements, the samples were also subjected to mechanical tests to verify the changes in the mechanical properties in terms of elastic behaviour of the selected steels when subjected to a static 3-point flexural test and Electron backscatter diffraction analysis (EBSD).
Keywords: Ultrasound speed; Thermal ageing; Elastic modulus E; Tree-point flexural test; Elastic stiffness coefficient